Applied naval architecture - Zubaly, R. B. (Cornell Maritime Press, 1996)
Applied Naval Architecture is intended for undergraduate students of many of the disciplines in maritime affairs, including marine engineering, marine transportation, nautical science, shipbuilding or ship production (shipyard apprentice schools), marine electrical engineering, meteorology, and oceanography. It could be used as an introduction to naval architecture for technical personnel of all types already employed in shipyards, and for licensed officers as a general reference and as preparation for license upgrading examinations. In short, its purpose is to describe what a naval architect does, and how he or she does it, to all students and practitioners involved in the business of merchant ships and shipping, except for professional naval architects themselves. Students preparing for a degree in naval architecture would also find the book useful as an introduction to their profession. - See more at: http://www.betterworldbooks.com/applied-naval-architecture-id-0870334751.aspx&utm_source=Affiliate&utm_campaign=Text&utm_medium=booklink&utm_term=3630151&utm_content=Homepage#sthash.e2JAHzYJ.dpuf